Leveraging on ENZ Metamaterials to Achieve 2D and 3D Hyper‐Resolution in Two‐Photon Direct Laser Writing. Issue 18 (30th March 2021) - Lio, Giuseppe Emanuele; Ferraro, Antonio; Ritacco, Tiziana; Aceti, Dante Maria; De Luca, Antonio; Giocondo, Michele; Caputo, Roberto
Abstract: A novel technique is developed to improve the resolution of two‐photon direct laser writing lithography. Thanks to the high collimation enabled by extraordinary εNZ (near‐zero) metamaterial features, ultrathin dielectric hyper‐resolute nanostructures are within reach. With respect to the standard direct laser writing approach, a size reduction of 89% and 50%, in height and width respectively, is achieved with the height of the structures adjustable between 5 and 50 nm. The retrieved 2D fabrication parameters are exploited for realizing extremely thin all‐dielectric metalenses tailored through deep machine learning codes. The hyper‐resolution achieved in the writing process enables the fabrication of a highly detailed dielectric 3D bas‐relief (with full height of 500 nm) of Da Vinci's "Lady with an Ermine". The proof‐of‐concept results show intriguing cues for the current and trendsetting research scenario in anti‐counterfeiting applications and ultracompact photonics, paving the way for the realization of all‐dielectric and apochromatic ultrathin imaging systems. Abstract : Two‐photon direct laser writing is enhanced to hyper‐resolution by leveraging on the extraordinary laser writing collimation enabled by εNZ metamaterials. The realization of ultrathin all‐dielectric metalenses and a highly detailed Da Vinci's "Lady with an Ermine" bas‐relief (500 nm full height) confirms full freedom in nanofabrication. These results show intriguing cues in trendsetting research scenarios and industry application.